Associations of serum gamma-linolenic acid levels with erythema severity and anxiety/depression status in patients with rosacea - Jin-Yi Tang; Mei-Ling Chen; Mei Wan; Jin-Yu Wei; Tian Qian; Yu-Kun Fan; Zhi Yang; Jian Fu; Jian Li (Sociedade Brasileira de Dermatologia, 2024)
Abstract Background The development of rosacea is suggested to be closely associated with lipid metabolism, inflammation, and anxiety/depression. Gamma linolenic acid (GLA) is a key factor participating in lipid metabolism, which is also confirmed to regulate the inflammatory response. However, the associations of serum GLA levels with rosacea severity and psychological status still remain unclear. Objective and limitations of the study The present study aimed to investigate the associations of gamma linolenic acid (GLA), a key factor participating in lipid metabolism and the inflammatory response, with rosacea severity and psychological status. The present study still had some limitations. First, this study is a cross-sectional study and does not provide longitudinal evidence about the relationship between GLA and rosacea; Second, the cohort in this study is also relatively small, and a larger cohort is needed in further investigation to reveal the potential role of lipid metabolism in the pathogenesis of rosacea. Methods A total of 62 rosacea patients were consecutively recruited. Patient's Self-Assessment (PSA) scale and Clinician Erythema Assessment (CEA) as well as 7-item Generalized Anxiety Disorder (GAD-7) and 9-item Patient Health Questionnaire (PHQ-9) were conducted to evaluate the degree of erythema severity and anxiety/depression, respectively. Serum GLA levels were determined by gas chromatography mass. Results Lower levels of serum GLA in rosacea patients were observed (p < 0.001), and subgroup analysis revealed that patients with higher-level GLA had lower scores of PSA, CEA, GAD-7 and PHQ-9. Moreover, Spearman correlation analysis uncovered that serum GLA levels were negatively associated with PSA, CEA, GAD-7 as well and PHQ-9 scores, respectively. Linear regression model found that serum GLA levels at baseline were a predictive factor for prognosis of clinical outcomes after 1-month conventional treatment. Conclusion The present study indicates that lower levels of serum GLA in rosacea patients are negatively associated with the degree of erythema and anxiety/depression status.